The utility of diffusion-weighted magnetic resonance imaging in differentiation of endometriomas from hemorrhagic ovarian cysts - Balaban, Mehtap; Idilman, Ilkay S.; Toprak, Huseyin; Unal, Ozlem; Ipek, All; Kocakoc, Ercan (Elsevier Science Inc, 2015)
The aim was to determine the utility of diffusion-weighted magnetic resonance imaging (DW MRI) and apparent diffusion coefficient (ADC) measurements in differentiation of endometrioma and hemorrhagic ovarian cyst. A total of 24 female patients who underwent pelvic MRI with an initial diagnosis of ovarian cyst were included in the study. The final diagnosis was endometrioma in 12 patients and hemorrhagic ovarian cyst in 12 patients. We observed significantly lower ADC values in endometriomas compared with hemorrhagic ovarian cysts in all b values. DW MRI with quantitative ADC measurements can be used for differentiation of endometrioma from hemorrhagic ovarian cysts. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Endometrioma; Hemorrhagic ovarian cyst; MRI; DWI and ADC